Mehmet Şemsettin Günaltay Hükümeti (1949-1950) - Nurçin, Emrah (My University, 2018)
Bu çalışmada, Cumhuriyet’in ilanından 14 Mayıs 1950 Genel Seçimlerine kadar iktidarda kalmış olan Cumhuriyet Halk Partisi’nin son hükümeti olan Mehmet Şemsettin Günaltay Hükümeti’nin siyasi, ekonomik ve sosyo-kültürel faaliyetleri ele alınmıştır.

In this study, the political, economic and socio-cultural activities of the Mehmet Şemsettin Günaltay’s Government, the last government of the Republican People's Party which remained in power from the proclamation of the Republic to general elections in 14th May 1950, have been addressed.
Keywords: 20 yy; 20th century; Coalition governments; Cumhuriyet Halk Partisi; Democratic Party; Demokrat Parti; Government; History; Hükümet Mehmet Şemsettin Günaltay; Koalisyon hükümetleri; Mehmet Şemsettin Günaltay; One Party; Political parties; Politics and government; Republican People's Party; Siyaset ve yönetim; Siyasi partiler; Tarih; Tek Parti; Turkey; Türkiye